Modus Operandi And Criminal Policy of Sexual Violence in Islamic Boarding Schools - Jamaludin, Ahmad (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2023)
This paper presents a research on the modus operandi of perpetrators of sexual violence in Islamic boarding schools, exploring the reasons and objectives behind these acts, as well as the criminal law policies applicable to these offenders. Sexual violence in these Islamic boarding schools requires prevention and intervention through a legal paradigm. Understanding the patterns of sexual violence in Islamic boarding schools is important to identify regulations and criminal sanctions for the perpetrators. It also helps to identify legal protections available to the victims. This research employs a socio-legal method that is analyzed descriptively and qualitatively, to provide answers to the issues discussed in this research. The findings of this research indicate that the modus operandi of sexual violence in Islamic boarding schools can be executed through persuasion, coercion, promises of marriage, transfer of knowledge, taking responsibility, or facilitating education up to university level, thereby deceiving and manipulating the victims into committing such immoral acts. Moreover, criminal law policies on sexual violence have been regulated by the Wetboek van Strafrecht, the Child Protection Law, Domestic Violence Law, the Sexual Violence Law, and the Criminal Code, with various forms of sanctions and protections, aimed at providing protection and justice for victims. Tulisan ini merupakan penelitian tentang modus operandi pelaku kekerasan seksual di Pesantren, apa alasan dan tujuan pelaku melakukan kekerasan seksual serta bagaimana kebijakan hukum pidana bagi pelaku kekerasan seksual di pesantren. Kekerasan seksual dipesantren memerlukan pencegahan dan penanggulangan dengan paradigma hukum, oleh karenanya perlunya diketahui modus operandi kekerasan seksual di pesantren agar dapat mengkualifikasikan regulasi mana dan sanksi pidana apa yang relevan diterapkan terhadap pelaku juga dapat memetakan perlindungan hukum apa yang bisa didapat korban kekerasan seksual di pesantren. Penelitian ini menggunakan metode sosio legal yang dianalisis secara deskriptif kualitatif sehingga dapat menemukan jawaban atas permasalahan yang akan dibahas dalam penelitian ini. Hasil penelitian ini adalah modus operandi kekerasan seksual dipesantren dapat dilakukan dengan membujuk rayu, memaksa mengiming-imingi akan dinikahi, ditransfer ilmu, bertanggung jawab dan akan memfasilitasi pendidikan sampai perguruan tinggi sehingga korban terperdaya dan mau melakukan perbuatan asusila tersebut. Selain itu kebijakan hukum pidana kekerasan seksual telah diatur oleh wetboek van strafrecht, UU Perlindungan Anak, UU PKDRT, UU TPKS dan KUHP dengan bentuk sanksi dan perlindungan yang beragam dengan tujuan memberikan perlindungan dan keadilan bagi korban.